The effect of photodiode shape on pinning potential for charge transfer in CMOS image sensors. (January 2023) - Liu, Lu; Yang, Shaohua; Yan, Ming; Li, Binkang; Guo, Yang; Guo, Mingan; Li, Gang; Zhou, Errui
Abstract: The effect of the pinned photodiode (PPD) shape on charge transfer has been investigated in this paper. By equating the change in pinning potential distribution due to PPD shape to the decrease in depth of the depletion region in the vertical direction, an analytical model of the PPD shape effect on the pinning potential is proposed. The model for a triangular-like PPD is validated by TCAD simulations and is in very good agreement with the simulation results. Based on the model results, a tower-shaped PPD shape that can obtain constant lateral electric field is given. Simulation results show that the tower-shaped PPD have good pinning potential variation linearity and much better charge transfer performance than rectangular and triangular PPDs. The model and analysis results in this paper provide theoretical support and design ideas for the shape design and optimization of PPD-based pixels to improve the charge transfer speed and reduce the image lag.